2008
DOI: 10.1016/j.brainres.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Fate of rubrospinal neurons after unilateral section of the cervical spinal cord in adult macaque monkeys: Effects of an antibody treatment neutralizing Nogo-A

Abstract: The present study describes in primates the effects of a spinal cord injury on the number and size of the neurons in the magnocellular part of the red nucleus (RNm), the origin of the rubrospinal tract, and evaluates whether a neutralization of Nogo-A reduces the lesionedinduced degenerative processes observed in RNm. Two groups of monkeys were subjected to unilateral section of the spinal cord affecting the rubrospinal tract; one group was subsequently treated with an antibody neutralizing Nogo-A; the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…Therefore, SMI-32 serves as a useful signal for rubrospinal neurons, especially for those in the caudal part. In a primate spinal cord injury study, SMI-32 antibody was used as a marker to label rubrospinal neurons (Wannier-Morino et al 2008). After unilateral section of the spinal cord, this study showed that the number of SMI-32-positive neurons was decreased.…”
Section: Anterograde Labelingmentioning
confidence: 99%
“…Therefore, SMI-32 serves as a useful signal for rubrospinal neurons, especially for those in the caudal part. In a primate spinal cord injury study, SMI-32 antibody was used as a marker to label rubrospinal neurons (Wannier-Morino et al 2008). After unilateral section of the spinal cord, this study showed that the number of SMI-32-positive neurons was decreased.…”
Section: Anterograde Labelingmentioning
confidence: 99%
“…These animals were part of several studies on the consequences of anti-Nogo-A antibody treatment on the regeneration of CS axons as well as on behavioral recovery after cervical cord injury. Separate data from 10 of these animals have appeared in previous reports (Freund et al, 2006(Freund et al, , 2007(Freund et al, , 2009Beaud et al, 2008;Wannier-Morino et al, 2008). Surgery and care of the animals were in conformity to the Guide for the Care and Use of Laboratory Animals (ISBN 0-309-05377-3; and authorized by local Swiss veterinary authorities.…”
Section: Experimental Procedures Animalsmentioning
confidence: 99%
“…30 -32 Schwab and colleagues subsequently developed an IgG anti-Nogo antibody for intrathecal application, which has been shown in rat and primate models of SCI to promote axonal sprouting and behavioral improvements. [33][34][35][36] This anti-Nogo IgG intrathecal approach has been commercialized by Novartis, who sponsored the initiation of an open label, nonrandomized human clinical trial currently being conducted as a multicenter study across Europe and in Canada (ClinicalTrials.gov Identifier: NCT00406016). SCI.…”
Section: Anti-nogo Antibodiesmentioning
confidence: 99%